Board reforms and firm employment: Worldwide evidence - Si, Yi; Yu, Minfeng; Zhang, Lei; Zhou, Qing (Clara) (Journal of Banking & Finance, 2025)
Managers often overreact to revenue fluctuations, leading to unnecessary workforce adjustments and increased training costs. This study examines how board governance influences firms’ employment sensitivity to revenue fluctuations. Analyzing global board reforms, we find that board reforms significantly reduce managerial overreaction to revenue fluctuations. Utilizing recent difference-in-differences estimators that address heterogeneous treatment effects, we ensure the robustness of our results. The reduction in employment sensitivity is more pronounced when board reforms strengthen the independence of boards and audit committees, particularly in jurisdictions with weaker board efficacy, shareholder, and employment protection legislation. Enhanced effects are observed in firms with initially lower board independence and rapid reform compliance, in entities experiencing greater information asymmetry, marked by higher labor intensity, higher pre-reform agency costs and financial constraints, and in firms led by less experienced CEOs or boards with higher male representation.